A Review and Critique of Book Can Education Change Society? - Alireza Assareh; Ali Rahbar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this study is to criticize the book  “Can Education Change Society?” written by Michael Apple in 2013. It was translated by Nazanin Mirzabaki (1395). This study reviews a critical tradition in the field of curriculum and educational studies. The research method and type of study are applied. In the first and second editions of the book,  one of the strengths of the book was the attempt to link political movements around the world to create changes, although the writer, translator,  and editor did a great job. Some of the textual and translation mistakes have led to criticism of the author and translator’s scientific approach. Perhaps the most important criticism of the author is the lack of use of scientific instruments, such as practice, charts, and pictures.